Awareness of Kidney Stone among Adults in a Ward of Changunarayan Municipality - Thayaju, Rabita; Sigdel, Sujita; Kayastha, Shrijana (Journal of Biratnagar Nursing Campus, 2025)
Introduction: Kidney stones are a common urological problem worldwide. It is a common problem seen in all ages, sexes, and races, but occurs more frequently in men than in women between the ages of 20–49 years. This study aimed to evaluate the level of awareness of kidney stone among adults in Changunarayan Municipality.Methods:  A Descriptive cross -sectional research design was used among 144 adults selected purposively from Changunarayan Municipality ward-3, Bhaktapur. A Self-developed structured interview questionnaire was used for data collection. The collected data were entered in statistical Package for the Social Sciences. The results were analyzed by using descriptive statistics, i.e., frequency, percentage, mean and standard deviation. Chi-square test was used to measure the associations between levels of awareness among adults with selected background variables.Results: Among 144 respondents, 42.4 % were from the age group 20-29 years with a mean age of 33.77± SD 8.26. Only 10.4 % had a previous history of kidney stones. Regarding the symptoms of kidney stones, 68.1% reported a strong desire to urinate. A total of 43.1% had inadequate awareness. There was no significant association between age, sex, education status, occupation, previous medical history, health problems and family history.Conclusion: This study revealed that nearly half of the adults had inadequate awareness. There was no statistically significant association between the level of awareness and selected background information. However, an awareness program focused on prevention could be conducted to increase the level of knowledge and reduce the incidence of kidney stone formation.